Efficacy and safety of ozone therapy for knee osteoarthritis: an umbrella review of systematic reviews - Lino, Valéria T. S.; Marinho, Daniel S.; Rodrigues, Nadia C. P.; Andrade, Carlos A. F. (Frontiers in Physiology, 2024)
The objective of this study is to evaluate the effectiveness and safety of ozone therapy (OT) in the treatment of knee osteoarthritis (KOA), which is the most common form of the disease. We analysed systematic reviews (SRs) of randomised controlled trials (RCTs) using the “A MeaSurement Tool to Assess systematic Reviews” (AMSTAR2) instrument to evaluate their quality. We developed a narrative synthesis report with eight SRs (15 RCTs/3,685 patients) to summarise the findings. The AMSTAR2 analysis indicated that all reviews had critically low confidence ratings. Statistically significant effects in pain reduction using OT compared to placebo groups were reported in three SRs. OT was shown to be comparable to other therapies in one SR and not superior in the other five. Six SRs highlighted the need for additional RCTs with improved methodological quality to confirm the efficacy of OT for KOA. SRs found fewer consistent effects for improving joint function. Regarding safety, seven SRs reported a low prevalence of minor adverse events linked with OT. Finally, this umbrella review highlights the beneficial effects and safety of OT in the treatment of KOA, particularly in pain control. The low methodological quality of RCTs and SRs limits the possibility of drawing conclusions on the effectiveness of the procedure in comparison to other therapies. Ensure adequate compliance with guidelines such as Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and AMSTAR2 has the ability to improve the quality of SRs in this area.